Predictive Algorithms in the Diagnosis and Management of Pediatric Hip and Periarticular Infection. (6th April 2022) - Hunter, Sarah; Kioa, Georgina; Baker, Joseph F.
Abstract : ➤ Although the criteria of Kocher et al. were an important advancement in our ability to diagnose septic arthritis of the hip early, the changing microbial landscape and availability of advanced imaging have rendered it insufficient for contemporary clinical use. ➤ Routine use of magnetic resonance imaging and recognition of disseminated disease have prompted the development of algorithms to predict concurrent osteoarticular infection in cases of septic arthritis and osteomyelitis that were previously assumed to be "isolated." ➤ Recent research has attempted to stratify childhood bone and joint infection (BJI) by severity to guide treatment planning. This is valuable, as patients with multifocal disease, more virulent pathogens, and immunocompromise can have longer hospital stays and require multiple surgeries. ➤ The increasing prevalence of clinical prediction algorithms in childhood BJI is not completely matched by quality in methodology. Clinicians need to be wary of adopting predictive algorithms prior to robust external validation.